EFFECT OF VOLATILE METABOLITES OF PHYLLOPLANE FUNGI OF CHLOROPHYTUM TUBEROSUM AGAINST ITS FUNGAL PLANT PATHOGEN IN-VITRO - SHIKHA THAKUR; N.S.K. HARSH (International Journal of Pharma and Bio Sciences, 2013)
Phylloplane fungi of Chlorophytum tuberosum were screened for their antagonistic activities against Colletotrichum dematium in vitro. Volatiles produced from the cultures of Trichoderma harzianum ISO-1 showed maximum inhibition of mycelial growth of C.dematium followed by T. piluliferum, T. harzianum ISO-2 and Aspergillus niger, respectively.